E-Voting Pemilihan Presiden Mahasiswa Pada BEM STMIK Syaikh Zainuddin NW Anjani - Yuliadi Yuliadi; Mohammad Taufan Asri Zaen; Mustakim Mustakim; Siti Patimah Az-zaen (JURIKOM (Jurnal Riset Komputer), 2021)
E-voting is an election system in which data is recorded, stored and processed in the form of digital information. The Student Executive Board (BEM) STMIK Syaikh Zaenuddin NW Anjani is an organizational forum to foster and direct students in the field of organization. Every year there will be a change of President BEM STMIK Syaikh Zaenuddin NW Anjani, direct elections are always carried out which are followed by all conventionally active students, namely students must come to campus to exercise their voting rights with a limited time burden and other problems. Based on these problems, an election system is needed that utilizes technology that is not limited to space and time, namely e-voting. E-voting system for the election of student presidents with technology to make it easier to make elections and minimize time efficiency, productivity, student learning on campus and reduce damaged ballots. The e-voting system uses the PHP programming language and uses a MySQL database.